Determinants of knowledge on Lassa hemorrhagic fever among medical students at the Faculty of Health Sciences at Cotonou in Benin - Noudohounsi, Mahugnon Maurel Ulrich Dénis; MONGBO, Virginie; Sossa-Jérôme, Charles (My University, 2021)
Background: Since 2014, Benin has experienced five epidemics of Lassa Hemorrhagic Fever (LHF), all of them have been fatal both in the community and in hospitals, in a context of inadequate health care safety and late diagnosis. The present research aimed to study the level of knowledge of medical students at the Faculty of Health Sciences in Cotonou on Lassa Hemorrhagic Fever. Methods: This was an analytical cross-sectional study of medical students, selected by stratified sampling. Data collected by selfadministered questionnaire were processed by Epi Info version 7.1.4.0 and analyzed in STATA/SE 11.2. The level of knowledge was assessed by scores, at a threshold of 65%, considered as the limit between good and bad knowledge. Multivariate logistic regression was used to identify the determinants of the level of knowledge obtained. Results: Out of 303 students surveyed, 25.38% (CI95%: 0.05; 0.46) had good knowledge of LHF. The epidemiology of this zoonosis was known by 30.94%, the diagnostic approach by 66.05%, the control measures by 28.67% and 10% of them knew that there was an effective curative treatment based on ribavirin if this is administered early. Training on LHF as a source of information was the only factor associated with the level of knowledge OR: 3.96 (CI95%: 1.41; 11.13). Conclusion: Given the low level of knowledge of students about LHF, there is a need for more emphasis on Viral Hemorrhagic Fevers in medical training programmes tailored to the different grades.
Keywords: Determinants of knowledge; Lassa Hemorrhagic Fever; Medical students; Benin